COMPARATIVE ANALYSIS OF SATISFACTION IN HOSPITAL TREATMENT AMONG CARDIOLOGICAL PATIENTS - Y. G. Shvarts; E. A. Naumova; E. V. Tarasenko (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate satisfaction in hospital treatment among cardiological patients and to compare the received data with results of the program Massachusetts Health Quality Partners (MHQP) Statewide Patient Survey, which is noted for high representation of the data (analysis of 12680 patient questionnaires obtained from 51 medical institutions of the state of Massachusetts).Material аnd methods. Questioning of patients in internal medicine clinic was carried out. We used Picker Institute questions, the same questionnaire which was used in program MHQP.Results. 376 patients took part in questioning. Preferences of cardiological patients did not differ from preferences of other therapeutic patients. On such criteria as respect for a patient, organization of treatment, rendering the information and physical comfort, satisfaction of our and American patients is quite comparable. Estimation of emotional support is somewhat lower at domestic patients. Involvement of a family to the treatment process is not sufficient both in our clinic, and in the American hospitals. All the patients were mostly unsatisfied in the process of discharge.Conclusion. The estimations of hospital treatment made by patients from clinics of different countries are similar very much. The process of discharge has got the lowest estimation by the surveyed patients. The form of final conversation and its environment require further analysis and correction.